STRATEGI PEMBELAJARAN YANG EFEKTIF DI SEKOLAH DASAR - Az-Zahra, Naisya; Sindy Yunika, Dwi; Syafira, Nayla; Aprisa, Loudia; Suriani, Ari; Safitri Syam, Salmaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore understanding of effective learning strategies with a focus on the central role of students. Effective learning is necessary to achieve educational goals. In the context of learning, challenges involve students' lack of understanding due to a focus on memorization without in-depth understanding. Teachers have a crucial role in addressing this problem by implementing learning strategies that encourage understanding and application of knowledge. This study used a qualitative approach to explore understanding of effective learning strategies with a focus on the central role of students. The results indicate that effective learning requires teachers to design engaging and student-focused learning. Learning quality is measured through aspects of student wellbeing, a supportive environment, appropriate program materials, a student-centered learning process, and holistic learning outcomes. Good learning strategies create positive impacts, including orderly classes, optimal resource utilization, and increased student motivation.